ALBANY, CHARTER AND GENERAL ORDINANCES, no. 152, § 8 (C. W. Watts 1887). - (:unkn) unknown (General Publisher, 1887)
That any person or persons who shall fire off or discharge any ordinary gun, pistol, rifle or other firearm within the corporate limits of the City of Albany, or shall ignite, fire or explode, or cause to be fired or exploded, any firecrackers, bombs, torpedoes or other fire or detonating works of any description whatever in that portion of the city bounded by Third Street on the south, Jackson Street on the east, Vine Street on the west and the Willamette River on the north, shall, upon conviction thereof before the Recorder's court, be fined not less than five or more than fifty dollars, or imprisoned in the city jail not less than two…**
--
Keywords: DISCHARGE